2020
DOI: 10.1007/s13300-020-00822-0
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab Pretreatment in Vitrectomy with Internal Limiting Membrane Peeling on Diabetic Macular Edema in Severe Proliferative Diabetic Retinopathy

Abstract: Aim: To evaluate the efficacy of intravitreal ranibizumab (IVR) pretreatment for pars plana vitrectomy (PPV) with internal limiting membrane (ILM) peeling in severe proliferative diabetic retinopathy (PDR) combined with macular edema (ME). Methods: Sixty-three patients with ME and PDR were divided into IVR and control groups. Three days before PPV stripping, ranibizumab was injected into the patients in the IVR group. The patients were followed for 6 months. The bestcorrected visual acuity (BCVA), visual acuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…It was revealed that the degree of CRT drop was linked to the improvement in BCVA (15) . Our study agrees with Guan et al (16) .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It was revealed that the degree of CRT drop was linked to the improvement in BCVA (15) . Our study agrees with Guan et al (16) .…”
Section: Discussionsupporting
confidence: 94%
“…There was a significant difference between the two groups in terms of surgical duration, intraoperative bleeding risk, iatrogenic retinal break incidence, endodiathermy frequency, and silicone oil tamponade rate (all P 0.05). In terms of postoperative complications, there was no discernible difference between the two groups (16) . Proliferative diabetic retinopathy patients with mild and moderate VH may benefit from intravitreal ranibizumab injections.…”
Section: Discussionmentioning
confidence: 76%
“…Guan et al [ 22 ] found that PPV with Lucentis preconditioning internal limiting membrane (ILM) peeling for severe proliferative DR complicated with macular edema (ME) could significantly ameliorate BCVA and CMT of patients and reduce postoperative complications such as operation time and intraoperative bleeding risk. Li et al [ 23 ] found that the combination of Lucentis and surgery for NVG can significantly control IOP and improve BCVA without serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal injection of anti-VEGF drugs 3 days before the operation may improve PPV results and facilitate ILM peeling. 30 In our study, for the same purposes, we injected IVR to all eyes 3 days before the PPV operation.…”
Section: Discussionmentioning
confidence: 99%